Реалії і перспективи Болонського реформування у ВНЗ України - Колесник, Юрій Михайлович; Нерянов, Юрій Михайлович; Авраменко, Микола Олександрович; Гейченко, Катерина Іванівна; Kolesnyk, Yu. M.; Nerianov, Yu. M.; Avramenko, M. O.; Heichenko, K. I. (My University, 2014)
У статті розглядається головна лінія розвитку вищої освіти України у контексті принципів Болонської системи, яка передбачає реалізацію концепції створення єдиного європейського освітнього простору. Описано реалії і перспективи впровадження болонського реформування на прикладі роботи Запорізького державного медичного університету, серед яких є якість вищої освіти, академічна інтеграція студентів і викладачів, наукова співпраця, інформатизація освітнього процесу. Відзначено позитивні моменти та проблеми стану сучасної освіти України з метою її вдосконалення і подальшої євроінтеграції. The article deals with the main direction of Ukrainian higher education development in the context of Bologna system, which presupposes creation of the common European higher education area. Realities and perspectives of the implementation of Bologna reforming are elucidated using the example of Zaporizhzhya State Medical University. These include quality of education, academic integration of students and teachers, scientific cooperation, informatization of educational process. Positive and negative aspects of modern Ukrainian education are pointed out with the aim of further perfection and European Integration.
Realities and perspectives of bologna reforming in ukrainian higher educational institutions